Postcard from Georg Bredig to Max Bredig, March 10, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) confirms that he has received his son's letter.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Chemists